2019
DOI: 10.3390/medicina55080438
|View full text |Cite
|
Sign up to set email alerts
|

Rising Trends in Hospitalizations for Cardiovascular Events among Young Cannabis Users (18–39 Years) without Other Substance Abuse

Abstract: Background and objectives: Modern-day epidemiologic data on the risk and shifting landscape of occurrence of cardiovascular events in cannabis users remain inadequate and rather conflicting, especially amongst the young adult population. Furthermore, the problem of polysubstance use among youth is challenging for healthcare professionals and policy-makers. Previous studies report higher risk of concomitant use of tobacco, alcohol, cocaine, and amphetamine in young cannabis users. However, most of these studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 17 publications
3
39
0
1
Order By: Relevance
“…Heavy marijuana users have a greater risk of developing palpitations compared to lighter users, with daily users having a relative risk of 2.2 (95% CI, 1.6-3.3; p-value < 0.0001) compared to a relative risk of 1.4 (95% CI, 1.1-1.9; p-value < 0.006) in occasional users [73]. A retrospective review of nearly 2.5 million patients in the National Inpatient Sample database found that 2.7% of marijuana users experienced arrythmias, with atrial fibrillation being the most common subtype [74]. Korantzopoulos et al reported an average age of 24 years old for patients experiencing cannabis-induced arrythmias, with all cases experiencing atrial fibrillation shortly after smoking marijuana [75].…”
Section: Cardiac Arrythmiasmentioning
confidence: 99%
“…Heavy marijuana users have a greater risk of developing palpitations compared to lighter users, with daily users having a relative risk of 2.2 (95% CI, 1.6-3.3; p-value < 0.0001) compared to a relative risk of 1.4 (95% CI, 1.1-1.9; p-value < 0.006) in occasional users [73]. A retrospective review of nearly 2.5 million patients in the National Inpatient Sample database found that 2.7% of marijuana users experienced arrythmias, with atrial fibrillation being the most common subtype [74]. Korantzopoulos et al reported an average age of 24 years old for patients experiencing cannabis-induced arrythmias, with all cases experiencing atrial fibrillation shortly after smoking marijuana [75].…”
Section: Cardiac Arrythmiasmentioning
confidence: 99%
“…Furthermore, in a nationwide retrospective cohort study done by Desai et al, consisting of 52,290,927 young patients from age 18 to 39 years, they found that the prevalence of AMI was greater (0.2% vs. 0.1%) in the marijuana users when compared with the non-users [45]. A prospective exploratory study of marijuana use and mortality following MI by Mukamal et al found out that marijuana use was associated with three times increased mortality following AMI [46].…”
Section: Incidence Of MI In Marijuana Usersmentioning
confidence: 97%
“…Thus, CB smoking increases the heart rate, the serum norepinephrine level and myocardial oxygen demand immediately, it reduces oxygen supply and leads to pro-coagulant or pro-thrombotic state, while the increased atropine inhibits the parasympathetic activity (12)(13)(14)(15)(16)(17). According to recent reports, the CB use might also cause dose-dependent elevation of the systolic blood pressure and heart rate (18,19) and induce atrial fibrillation shortly after smoking MJ (20). While smoking CB, the oxygen delivery to the heart and other vital organs is diminished and the carboxyhemoglobin levels are elevated, resulting in reduce of the time to onset of symptoms during exercise in patients with stable angina (12).…”
Section: Cardiovascular Effects Of Cannabinoids (Cb) Physiologymentioning
confidence: 99%